"I ain't sorry": African American English as a strategic resource in Beyoncé's performative persona. (May 2020) - Eberhardt, Maeve; Vdoviak-Markow, Madeline
Abstract: In this paper, we examine the role language plays in the development of the performative persona of musical artist Beyoncé, as she moves from female pop star to Black Feminist icon. Examining Beyoncé's five solo albums, we present a variationist analysis of a single feature, zero copula, and its use over the course of her career. We argue that this feature is an important symbolic resource for the assertion of an unapologetically Black and feminist persona. As Beyoncé has moved steadily away from popular expectations for representations of Black womanhood, language is a central tool that she uses strategically in the evolution of a newly transgressive persona. Highlights: Examines variation in zero copula over the course of the musical career of the cultural icon Beyoncé. Is an important symbolic resource for the assertion of an unapologetically Black and feminist persona. Manipulation of AAVE is a central tool that Beyoncé uses strategically in the evolution of a newly transgressive persona.